Pengaruh Permainan Puzzle Terhadap Perkembangan Kognitif Anak Kelompok B1 di RA Fastabiqul Khairat - Marwati, Shopa; Purbayani, Rini; Herniawati, Ani (JOECE: Journal of Early Childhood Education, 2025)
This study aims to determine the cognitive development of early childhood before and after using puzzle games, and to determine the effect of puzzle games on the cognitive development of early childhood. The method used is quantitative, with the type of research pre-experimental design with a One-Group pretest-posttest design. The sampling technique used a saturated sample of 14 children. Data were collected through observation sheets, then analyzed quantitatively using the Wilcoxon test with the help of SPSS. The results showed that during the pretest, 71.43% of children were in the category of Not Developing (BB) and 28.57% of children were in the category of Starting to Develop (MB). After using the puzzle game, the posttest results showed 42.86% of children were in the Developing As Expected (BSH) category and 57.14% of children were in the Very Good Developing (BSB) category. The Wilcoxon test results show a sig value of 0.001, which means that Ha is accepted and Ho is rejected. Thus, it can be concluded that puzzle games have an effect on children's cognitive development in group B1 at RA Fastabiqul Khairat.